A DIMENSÃO COLABORATIVA NO MOVIMENTO DE ENSINAR, APRENDER E FORMAR-SE PROFESSOR QUE ENSINA MATEMÁTICA - Halana Garcez Borowsky Vaz; Anemari Roesler Luersen Vieira Lopes; Diaine Susara Garcez da Silva (Universidade do Oeste de Santa Catarina, 2012)
Our concern about mathematics teaching and learning and the training of teachersinvolved in mathematics educational processes led to the creation of a group thatdevelops research and extension projects, one of them is the Mathematics Club. It isdeveloped in a School of Basic Education in a collaborative dimension and it countswith a teacher and ungraduated teachers participation. Trying to understand to whatextent the participation of these persons contribute to their formation, we developeda research and a cut from it is presented in this paper that has as the main objectiveto investigate how the teachers and the ungraduated teachers perceive their insertionin the Mathematics Club, in relation to their learning of teaching. The data wereobtained through interviews with the involved persons. The data analysis showed thatthe teacher and the ungraduated teachers associate some aspects of their learningof teaching to their inclusion in this project, especially in the planning process andthe interaction among the persons involved in the working group, the result leads usto understand collaborative dimension as a possibility of educational processes thatcontributes to the learning of teaching.